Reimagining South African higher education: towards a student-centred learning and teaching future - (:unkn) unknown (Sun Press, 2024)
Reimagining South African Higher Education: Towards a Student-Centred Learning and Teaching Future provides progressive approaches and innovations that challenge readers to rethink student learning, engagement, support, and teaching. The book offers examples of evidence-informed and scholarly approaches to centring students through enhanced learning and teaching practices that are relevant to the South African context and those Global South contexts similar to South Africa.
Open Educational Resource
Keywords: Higher Education; Teaching and Learning; Student engagement; Student success; South Africa; SDG-4: Quality education